2011
DOI: 10.1097/qad.0b013e3283489d1f
|View full text |Cite
|
Sign up to set email alerts
|

The effect of HIV infection and HAART on inflammatory biomarkers in a population-based cohort of women

Abstract: Objective HIV causes inflammation that can be at least partially corrected by HAART. To determine the qualitative and quantitative nature of cytokine perturbation, we compared cytokine patterns in three HIV clinical groups including HAART responders (HAART), untreated HIV non-controllers (NC), and HIV-uninfected (NEG). Methods Multiplex assays were used to measure 32 cytokines in a cross-sectional study of participants in the Women's Interagency HIV Study (WIHS). Participants from 3 groups were included: HAA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

20
101
4
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 121 publications
(126 citation statements)
references
References 50 publications
20
101
4
1
Order By: Relevance
“…In another South African-based study INF-g, IL-6 and IL-10 were elevated in a group of HIV-infected individuals with immune reconstitution inflammatory syndrome [16]. IL-2 and IL-6 were key cytokines elevated in simian immunodeficiency virus-infected monkeys with encephalitis [12]. These examples supports IL-6 and IL-10 levels as having a role in the immune response against HIV infection and potentially also in monitoring disease progression.…”
Section: Resultsmentioning
confidence: 48%
See 2 more Smart Citations
“…In another South African-based study INF-g, IL-6 and IL-10 were elevated in a group of HIV-infected individuals with immune reconstitution inflammatory syndrome [16]. IL-2 and IL-6 were key cytokines elevated in simian immunodeficiency virus-infected monkeys with encephalitis [12]. These examples supports IL-6 and IL-10 levels as having a role in the immune response against HIV infection and potentially also in monitoring disease progression.…”
Section: Resultsmentioning
confidence: 48%
“…Similar to Jansen et al [25], it seems that viral load is the driving force determining the extent of the immune response. Keating et al [12] also showed this influence of viral load on the extent of cytokine perturbation (cytokines were less altered when viremia was lowered through treatment).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These results can also be linked to anti-HIV properties of this plant; low levels of IL-17A in HIV-1 infection is associated with non-progression (Yue et al, 2008). IL-17A along with other cytokines such as IL-2 and IL-6 are elevated during the different stages of HIV infection (Keating et al, 2011;Nixon and Landay, 2010;Worsley et al, 2010;Yue et al, 2008). Therefore lowering the production of this cytokines especially IL-17A could contribute to slow or nonprogression of HIV infection.…”
Section: P Barbatus Inhibits Pro-inflammatory Cytokinesmentioning
confidence: 99%
“…They can accelerate the immune response against the virus [17], while simultaneously, cytokine activity amplifies the population of target cells for HIV infection by activating CD4+ T-cells. In chronic HIV infection, elevated concentrations of proinflammatory cytokine TNF-α and its receptor TNF-RII indicate long-term inflammation in infected persons [18] and [19].…”
Section: Introductionmentioning
confidence: 99%